2018
DOI: 10.31018/jans.v10i1.1573
|View full text |Cite
|
Sign up to set email alerts
|

Impact of planting density on wheat crop grown under different tree species in tarai agroforestry system of central himalaya, India

Abstract: Abstract:A field trial based Agroforestry system was established at Pantnagar during Rabi season 2012-13 for predicting the effect of spacing on growth and yield of wheat (Triticum aestivum L.) under Eucalyptus camaldulensis and Melia azedarach. The experiment was carried out in split-plot design consisting of two tree species in main plot, viz, Eucalyptus camaldulensis and Melia azedarch and four spacing treatments in sub-plot viz, 3.0m×1.0m, 3.0m×1.5m, 3.0m×2.0m and 3.0m×2.5m with three replications. The whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The loss in crop yield under eucalypts can be compensated by the income returns from the tree component at the end of the rotation. Satyawali et al, (2018) also reported that eucalypts based agroforestry system fetched higher net retruns as compared to melia.…”
Section: Resultsmentioning
confidence: 86%
“…The loss in crop yield under eucalypts can be compensated by the income returns from the tree component at the end of the rotation. Satyawali et al, (2018) also reported that eucalypts based agroforestry system fetched higher net retruns as compared to melia.…”
Section: Resultsmentioning
confidence: 86%